Early Devonian (~410 mya) microfossils resembling Characiopsis (Tribophyceae) and Characium (Chlorophyceae). Issue 3 (29th March 2017) - Krings, Michael; Harper, Carla J.; Taylor, Edith L.; Kerp, Hans
Abstract : Unusual microfossils that occurred associated with fungal spores in the Lower Devonian (~410 mya) Windyfield chert from Scotland were composed of a narrow stipe (2.5–9 μm long) to which was attached an obovoid or elongate drop‐shaped cell up to 14 μm long; a basal attachment pad was present in several specimens. The fossils were strikingly similar morphologically to certain present‐day unicellular freshwater Tribophyceae and Chlorophyceae, but affinities to the fungal phylum Chytridiomycota also cannot be ruled out. This discovery adds to the inventory of distinctive microbial morphologies in the early non‐marine paleoecosystems.